Applicability of Sediment Transport Capacity Models for Nonsteady State Erosion From Steep Slopes - Tayfur, Gökmen; Tayfur, Gökmen (American Society of Civil Engineers (ASCE), 2002)
The physics-based sediment transport equations are derived from the assumption that the sediment transport rate can be determined by a dominant variable such as flow discharge, flow velocity, slope, shear stress, stream power, and unit stream power. In modeling of sheet erosion/sediment transport, many models that determine the transport capacity by one of these dominant variables have been developed. The developed models mostly simulate steady-state sheet erosion. Few models that are based on the shear-stress approach attempt to simulate nonsteady state sheet erosion. This study qualitatively investigates the applicability of the transport capacity models that are based on one of the commonly employed dominant variables-unit stream power, stream power, and shear stress-to simulate nonsteady state sediment loads from steep slopes under different rainfall intensities. The test of the calibrated models with observed data sets shows that the unit stream power model gives better simulation of sediment loads from mild slopes. The stream power and the shear stress models, on the other hand, simulate sediment loads from steep slopes more satisfactorily. The exponent (ki) in the sediment transport capacity formula is found to be 1.2, 1.9, and 1.6 for the stream power model, the shear stress model, and the unit stream power model, respectively.
Keywords: Erosion; Sediment transport; Shear stress; Slopes